2008
DOI: 10.3121/cmr.2008.752
|View full text |Cite
|
Sign up to set email alerts
|

The Neglected Femoral Neck Fracture in Young Adults: Review of a Challenging Problem

Abstract: A neglected femoral neck fracture is one where there has been a delay of more than 30 days to seek medical help from the time of the original injury. Among the spectrum of femoral neck fractures, the neglected fracture in a young adult (age <60 years) is one of the most challenging to treat if femoral head salvage is attempted.The main complication is avascular necrosis (AVN) of the femoral head with most reported incidences being <15% (range 0% to 67%), which is similar to the complication rate with non-negle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 34 publications
1
51
0
2
Order By: Relevance
“…7 Salvaging the femoral head for younger adults (<60 years of age) with neglected femoral neck fractures is challenging. 8 Total hip arthroplasty is recommended for those older than 60 years, although the appropriate treatment should depend not only on patient age, but also medical status, viability of the femoral head, size of the remnant femoral neck, extent of osteoporosis, duration of the disease, and the state of the joint space. 9 Osteosynthesis such as valgus osteotomy, [10][11][12][13] fibular grafting with internal fixation, 14 vascularised bone grafting, [15][16][17] muscle pedicle bone grafting, 18 McMurray displacement osteotomy 19 have been advocated for neglected femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…7 Salvaging the femoral head for younger adults (<60 years of age) with neglected femoral neck fractures is challenging. 8 Total hip arthroplasty is recommended for those older than 60 years, although the appropriate treatment should depend not only on patient age, but also medical status, viability of the femoral head, size of the remnant femoral neck, extent of osteoporosis, duration of the disease, and the state of the joint space. 9 Osteosynthesis such as valgus osteotomy, [10][11][12][13] fibular grafting with internal fixation, 14 vascularised bone grafting, [15][16][17] muscle pedicle bone grafting, 18 McMurray displacement osteotomy 19 have been advocated for neglected femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture non-union after internal fixation has been attributed to several reasons including inadequate biomechanical and vascular conditions, poor reduction and unfavourable internal fixation [3]. Moreover, negligence in the developing world may add another reason for much higher incidence [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It converts the vertical shear force into a horizontal compressive force and promotes union. However, it alters the biomechanics of the hip joint and causes shortening, limp and a decreased range of movement, probably because of increased pressure on the femoral head leading to degenerative disease or osteonecrosis [1,2]. Considering the long-term problems of osteotomy, Roshan et al suggested that bone grafting with internal fixation is still the reliable method of fixation in femur neck nonunion [2].…”
Section: Valgus Intertrochanteric Osteotomy May Be Consideredmentioning
confidence: 99%